Studies on Schistidium (Grimmiaceae, Bryophyta) in Europe, with particular reference to the Alps: II. Description of two new species S. pratense and S. heribertii - Blom, Hans H.; Kiebacher, Thomas; Bednarek-Ochyra, Halina; Ochyra, Ryszard (Phytotaxa, 2025)
Schistidium pratense and S. heribertii, two distinctive and locally abundant components of the Alpine flora, are here formally described as new species from Europe. Although recognised for over two decades, their official taxonomic treatment has been long overdue. This paper provides an integrative account, combining morphological and molecular evidence, outlining their currently known distribution, and discussing their relationships to related species. Schistidium pratense is closely allied to S. dupretii in both molecular and morphological traits but differs in its larger overall size, including longer shoots and leaves, as well as in the absence of stomata. Schistidium heribertii resembles S. atrofuscum in its black coloration but is distinguished by its prominent leaf hairpoints and a pruinose appearance on the upper parts of the shoots. Molecular analyses place S. heribertii as the sister species to the clade comprising S. atrofuscum and S. helveticum. Both new species share similar ecological preferences, typically colonising calcareous substrates. Schistidium pratense is widespread and locally abundant in subalpine pastures, while S. heribertii has a more scattered distribution and predominantly inhabits warm sites across a broad elevational range in valleys with a continental climate. To date, S. heribertii is known only from the Alps, whereas S. pratense has also been recorded in Scandinavia, the Dinarides, the Apennines and the Black Forest in Germany.